2022
DOI: 10.1111/jgh.15880
|View full text |Cite
|
Sign up to set email alerts
|

Minimal risk of lymphoma and non‐melanoma skin cancer despite long‐term use of thiopurines in patients with inflammatory bowel disease: A longitudinal cohort analysis from northern India

Abstract: Background and Aim Thiopurines are widely used to maintain remission in both ulcerative colitis (UC) and Crohn's disease (CD). Reported effectiveness and tolerability rates have been variable across studies. There are only sparse data in Asian population regarding the long‐term efficacy and safety of thiopurines. Methods Records of 5351 patients followed up at inflammatory bowel disease (IBD) clinic, All India Institute of Medical Sciences, New Delhi from 2004 to 2020 were evaluated retrospectively. Safety was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The risk of Epstein–Barr virus‐associated hepatosplenic T‐cell lymphoma can be mitigated by avoiding thiopurines in young males negative for Epstein‐Barr virus (EBV) serology at baseline. The risk of malignancy may be dependent on the geography and may not be very common in Asians, as reported in a recent retrospective cohort study from northern India, where no case of lymphoma or NMSC was reported over 4788 person‐years of follow‐up 37 . Hence, thiopurines may be continued if patients tolerate and respond under close monitoring for adverse events, as thiopurine withdrawal is associated with the risk of relapse in 50% patients 38 …”
Section: Genetic Polymorphisms Impacting Thiopurine Metabolismmentioning
confidence: 99%
“…The risk of Epstein–Barr virus‐associated hepatosplenic T‐cell lymphoma can be mitigated by avoiding thiopurines in young males negative for Epstein‐Barr virus (EBV) serology at baseline. The risk of malignancy may be dependent on the geography and may not be very common in Asians, as reported in a recent retrospective cohort study from northern India, where no case of lymphoma or NMSC was reported over 4788 person‐years of follow‐up 37 . Hence, thiopurines may be continued if patients tolerate and respond under close monitoring for adverse events, as thiopurine withdrawal is associated with the risk of relapse in 50% patients 38 …”
Section: Genetic Polymorphisms Impacting Thiopurine Metabolismmentioning
confidence: 99%
“… Forest plot of IBD incidence. IR, Incidence Rate; SE, Standard Error ( 4 , 6 , 9 , 11 , 23 27 , 29 34 , 36 45 , 48 , 50 , 51 , 57 ). …”
Section: Resultsmentioning
confidence: 99%
“… 22 However, most recently, a longitudinal cohort analysis from north India, which evaluated 1093 IBD patients on AZA with a median follow‐up of 7 years, reported that not a single patient on AZA developed lymphoma or NMSC. 51 Thus, at present, it may be safe to conclude that the benefits of long‐term immune modulation with AZA significantly outweigh the minor risk of malignancy in patients with IBD.…”
Section: Discussionmentioning
confidence: 99%